The Mediating Role of Hostile Attribution Bias in the Association between Personality and Cyber-bullying - Κόκκινος Κωνσταντίνος; Αντωνιάδου Ναυσικά; Βουλγαρίδου Ιωάννα (Psychology: the Journal of the Hellenic Psychological Society, 2019)
The aim of this study was to investigate the association of the Big Five personality traits, Hostile Attribution Bias, and cyber-bullying among 347 Greek students attending the last grade of primary school and Junior High School. In order to explore whether the effect of personality traits on cyber-bullying is better explained through Hostile Attribution Bias, a mediation analysis was run. Results showed that Hostile Attribution Bias mediated the links between high Neuroticism, and low Extraversion on the one hand and cyber-bullying on the other. Overall, findings suggest that individuals low in Emotional Stability and less sociable are more likely to manifest cyber-bullying due to their tendency to attribute hostile intent, which may be exacerbated during computer mediated communication, which frequently provides limited social cues to the user. Findings can contribute towards the prevention and intervention of cyber-bullying through programs which help students interpret ambiguous social interactions.